2010
DOI: 10.1097/bor.0b013e32833f1075
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy and myositis: novel autoantibodies and new insights

Abstract: Advances in immunology and imaging techniques are increasing the accuracy of occult malignant cancer detection in dermatomyositis patients. Nevertheless, the diagnosis of cancer in this population remains elusive in some cases. Further investigation is needed to improve our knowledge of the link between myositis and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 37 publications
0
44
2
9
Order By: Relevance
“…The clinical manifestations of this reactivity involve high prevalences in dermatomyositis, as reported by Targoff et al, but with a high specificity the occurrence of this MSA correlates with a risk of malignancies as (Kaji et al, 2007). This observation was statistically underlined when Selva O´Canaghan et al performed a meta analysis for anti TIF 1 gamma antibodies and predictive values for malignancies (Selva-O'Callaghan et al, 2010) and found that anti p155/TIF1 y antibodies have a 70 % sensitivity and a 90 % specificity to detect occult malignancies in DM. The TIF1 gamma protein as described by Venturini et al shows a strong silencing activity towards gentic promoter sequences.…”
Section: Tif1 Gammamentioning
confidence: 84%
“…The clinical manifestations of this reactivity involve high prevalences in dermatomyositis, as reported by Targoff et al, but with a high specificity the occurrence of this MSA correlates with a risk of malignancies as (Kaji et al, 2007). This observation was statistically underlined when Selva O´Canaghan et al performed a meta analysis for anti TIF 1 gamma antibodies and predictive values for malignancies (Selva-O'Callaghan et al, 2010) and found that anti p155/TIF1 y antibodies have a 70 % sensitivity and a 90 % specificity to detect occult malignancies in DM. The TIF1 gamma protein as described by Venturini et al shows a strong silencing activity towards gentic promoter sequences.…”
Section: Tif1 Gammamentioning
confidence: 84%
“…14 In contrast, in adults, reports of malignancy in association with adult dermatomyositis and, to a much lesser extent, polymyositis, have ranged from 10% to 42% of cases. 5,8,14,15 In 618 adults with adult dermatomyositis, there was a strong association with ovarian tumors (most of them adenocarcinomas) followed by lung cancer, gastrointestinal cancers, and non-Hodgkin lymphoma. 8 In adults with myositis, but not children (as in this case), myositisspecific antibody to p155/140 seemed to be a prognostic factor for malignancy, and ethnicity strongly influenced the type of malignancy found.…”
Section: Discussionmentioning
confidence: 99%
“…Myositisoverlap syndromes also present with myalgias and weakness in conjunction with other rheumatologic diseases such as rheumatoid arthritis or systemic lupus erythematosus [Gherardi, 2011]. Malignancy must also be considered in patients presenting with weakness and myalgias because the incidence of new cancer is higher in patients with IIM [Selva-O'Callaghan et al 2010;Zahr and Baer, 2011]. Drug-induced or toxic myopathies can present with acute or subacute muscle weakness, myalgia, elevated CK levels and/or myoglobinuria [Valiyil and Christopher-Stine, 2010].…”
Section: Myositis Mimics/differential Diagnosismentioning
confidence: 99%